Implementasi Program Penataan Ruang Terbuka Hijau Publik di Kecamatan Candisari Kota Semarang - Nimas, Veronica; Kismartini, Kismartini; Maesaroh, Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
The purpose of this research is to analyse the implementation of program of green public areas arrangement in Cnadisari Sub District of Semarang and to know the factors that affect this implementation. To solve the the problems and to gain the aims of this research, the researcher used green open space utilization community, compatibility with the planning of program and the control of the implementation program itself. The researcher focused on the subject of the program on how the program is implemented. The researcher also pay attention to some factors that influence this research. The factors are communication, bureaucratic structure, resource and predisposition. This research used qualitative research and descriptive method. The result of this study shows that the implementation program of green open space in Candisari sub district, Semarang have not done well. The minimum percentage of green open space have not achieved yet. Some of causes are the advantages of green open space itself are not used maximally by the public, the lack of public participation to support this program, the lack of human resources who take in charge in this program, the funds which is not provided sufficiently and the lack of control from government.